2000
DOI: 10.1200/jco.2000.18.2.348
|View full text |Cite
|
Sign up to set email alerts
|

New Malignant Diseases After Allogeneic Marrow Transplantation for Childhood Acute Leukemia

Abstract: Long-term survivors of BMT for childhood leukemia have an increased risk of solid cancers and PTLDs, related to both transplant therapy and treatment given before BMT. Transplant recipients, especially those given radiation, should be monitored closely for second cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
244
3
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 304 publications
(262 citation statements)
references
References 42 publications
11
244
3
4
Order By: Relevance
“…11,19,[20][21][22][23][24] Radiation and chemotherapy used for treatment of primary disease and in conditioning regimens, as well as profound immunosuppression post allo-HSCT have been identified as contributing factors. 19,20 In our cohort (429 patients), the CI rate of secondary malignancy was 4.3% at 17.6 years with a median time of 6.8 years post allo-HSCT (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…11,19,[20][21][22][23][24] Radiation and chemotherapy used for treatment of primary disease and in conditioning regimens, as well as profound immunosuppression post allo-HSCT have been identified as contributing factors. 19,20 In our cohort (429 patients), the CI rate of secondary malignancy was 4.3% at 17.6 years with a median time of 6.8 years post allo-HSCT (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…The reported rate in the literature ranges from 6.1 to 12.8%. 4,6,8,[15][16][17] This difference might be attributable to the fact that our cohort was strictly pediatric. Comparable rates to those observed in our study were reported in a single study of pediatric and adults survivors of allogeneic transplant (15-year incidence of 2.2%).…”
Section: Discussionmentioning
confidence: 99%
“…4,[6][7][8][9] Those studies that report on pediatric populations consistently report an inverse relationship between age at transplantation and risk of post-HSCT SMN. 4,6,8 However, little is known about the independent contribution of HSCT to the development of SMNs. It is important to characterize and compare the risk of developing SMN in children with malignancies treated with and without HSCT to understand any differences in risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being at risk after radiation therapy alone, chemotherapy alone and combined chemo-and radiotherapy, these risks apply to patients who undergo HSCT at a younger age, 48 although a genetic predisposition may have a role in the development of second malignant neoplasms. 49 Socie`et al 50 reported higher risk of occurrence of solid tumours in paediatric patients transplanted below the age of 5 years. Cancer of the brain and thyroid did represent half of all secondary tumours occurring most frequently in very young transplanted patients.…”
Section: Second Malignant Neoplasmsmentioning
confidence: 99%